Nuclear Tau, p53 and Pin1 Regulate PARN-Mediated Deadenylation and Gene Expression - Baquero, Jorge; Varriano, Sophia; Ordonez, Martha; Kuczaj, Pawel; Murphy, Michael R.; Aruggoda, Gamage; Lundine, Devon; Morozova, Viktoriya; Makki, Ali Elhadi; Alonso, Alejandra del C.; Kleiman, Frida E. (Frontiers in Molecular Neuroscience, 2019)
While nuclear tau plays a role in DNA damage response (DDR) and chromosome relaxation, the mechanisms behind these functions are not fully understood. Here, we show that tau form complex(es) with factors involved in nuclear mRNA processing such as tumor suppressor p53 and PARN deadenylase. Tau induces PARN activity in different cellular models during DDR, and this activation is further increased by p53 and inhibited by tau phosphorylation at residues implicated in neurological disorders. Tau’s binding factor Pin1, a mitotic regulator overexpressed in cancer and depleted in Alzheimer’s disease (AD), also plays a role in the activation of nuclear deadenylation. Tau, Pin1 and PARN target the expression of mRNAs deregulated in AD and/or cancer. Our findings identify novel biological roles of tau and toxic effects of hyperphosphorylated-tau. We propose a model in which factors involved in cancer and AD regulate gene expression by interactions with the mRNA processing machinery, affecting the transcriptome before the appearance of traditional markers of disease.